Uncertainty Kills the Cake: Economy and Society After Brexit and Beyond - Onaran, Özlem (Border Crossing, 2025)
This article discussed the key political issue limiting a genuine assessment of Brexit, in particular the divergence between the political narratives around migration and the facts regarding the actual economic impacts of migration, and the economic effects of labour vs. capital mobility. Moving forward, the article discusses political options regarding Britain’s relationship with the EU suggesting membership to the Customs Union and Single Market. The article concludes with an alternative building on a green, purple, red new deal for radical abundance to challenge the current status quo and pave the way for a democratic discussion on Britain’ rejoining the EU.